Tubaramure, a food-assisted integrated health and nutrition program, reduces child wasting in Burundi: A cluster-randomized controlled intervention trial - Leroy, Jef L.; Olney, Deanna K.; Nduwabike, Noé; Ruel, Marie T. (American Society for Nutrition, 2021)
Little is known about the impact of food-assisted maternal and child health programs (FA-MCHN) on child wasting. We assessed the impact of Tubaramure, a FA-MCHN program in Burundi, on child (0 to 24 months) wasting and the differential impacts by socio-economic characteristics and age. The program targeted women and their children during the first 1000 days and included 1) food rations, 2) strengthening and promotion of use of health services, and 3) behavior change communication (BCC).